Pendidikan Agama Islam dan Budi Pekerti Melalui Psikodrama Materi Kisah Teladan Luqman Untuk Meningkatkan Rasa Bersyukur Siswa - Syu'aib Nawawi (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Imbalances in education indirectly split the personality of children from kindergarten to college. The preferred objectives are the mastery of the material / information, along with the teaching approach being pursued by the target and achievement of the standard. The evaluation system dictates the process, so the accumulative impact that is felt after a person attending many years of education until graduation from the PT for example is, someone who became a scholar, but not a full scholar who is able to think holistically in overcoming real life problems facing him, let alone participate in solving social problems. This study aims to describe the Islamic Religious Education and Character through Psychodrama Luqman role model to Improve the sense of grateful students. This research includes field research and uses a qualitative descriptive approach. The subjects of this study are SDN Mojosari 1 and 2. The time of this study is even semester of academic year 2017/2018. Data collection method in this research is observation. Data analysis of secondary data, searching and organizing systematically transcripts / records of observations and other materials to improve the author's understanding of the case studied and review it as a finding for others. The results of this study are: that different from other techniques, in psychodrama emotional weight is more highlighted than the intellectual weight. The cultivation of gratitude, especially gratitude requires a long process, in the first phase the teacher starts PBM by praying to instill awareness and gratitude for God's greatness, the teacher motivates the students with the initial activities related to the material. students who are motivated to learn something will use a higher cognitive process in learning the material so that the student will better absorb and listen to the material.